Investigating English language teachers’ language assessment literacy and conceptions of assessment in Mozambique. - Muianga, Felizardo Armando (2024)
Abstract Assessment literacy and conceptions of assessment are central to the successful implementation of formative assessment initiatives. Assessment literacy enables teachers to translate theory into practice. On the other hand, conceptions shape understanding, interpretation, and implementation of new assessment policies. This mixed-methods study examined secondary school English language teachers’ assessment literacy and conceptions of assessment in Maputo, Mozambique. The quantitative data were collected through a survey involving 80 teachers. The qualitative data were gathered through in-depth interviews and observation involving 12 participants. The findings show that the teachers’ experience with formal training in language assessment differed significantly. Some participants reported not receiving any sort of formal training in language assessment, while others indicated receiving training in both formal and informal assessment. Additionally, some teachers reported receiving